GREENHOUSE GAS EMISSION AND THE SDGs: HOW ENVIRONMENTAL PERFORMANCE SHAPE CORPORATE VALUE - Damas, Dading; Rahardja, Liana; Lawita, Florencia; Victoria, Nadia (JRAK, 2025)
The research problem arises from growing investor concern over the environmental risks of greenhouse gas (GHG) emissions and the long-term value of strong Sustainable Development Goals (SDGs) practices. This study examines the effect of GHG emissions and SDG practices on firm value, with environmental performance as a moderating variable. The sample includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) that consistently participate in the PROPER program. using purposive sampling and multiple linear regression analysis, the findings show that GHG emissions negatively affect firm value, while sustainability practices have a positive effect. Furthermore, environmental performance strengthens both the negative effect of GHG emissions and the positive effect of SDG practices on firm value. These results emphasize the theoretical role of environmental and sustainability factors in firm valuation and provide practical implications for managers and regulators to view environmental initiatives as value drivers.